ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN (Students' Journal of Accounting and Banking, 2012)
The purpose of this study to analyze the factors that affect dividend policy, which includes profitability ratios (ROA), liquidity (CR), solvency (DER), and activity (ATO).The population in this study is a manufacturing company listed on the Indonesia Stock Exchange and the sample period 2007-2010 is the company distributing dividends in 2008-2010. Of firms that enter the criteria in the study sample was 37 manufacturing companies. The analysis used in this study is the Multiple Linear Regression.The results of this study, independent of the four factors studied (ROA, CR, DER, ATO) ROA variables that have a significant positive impact on dividend policy, while the other variables CR, DER, and the ATO does not affect the dividend policy (DPR).Keywords: DPR, ROA, CR, DER, ATO.